KETIMPANGAN PENGUASAAN LAHAN SEBAGAI TANTANGAN PERLINDUNGAN PETANI DALAM KERANGKA HUKUM PERTANIAN INDONESIA - Saptaning Ruju Paminto; Ardelia Lananda (LPPM Universitas Doktor Husni Ingratubun Papua, 2026)
Inequality in agricultural land ownership in Indonesia is a structural issue that directly weakens the bargaining position and economic access of smallholder farmers. Although Indonesia's agrarian legal framework normatively affirms the principles of social justice, the social function of land, and restrictions on land ownership, land ownership and control remain concentrated in certain groups. This situation raises questions about the extent to which agricultural law is able to provide equitable protection for farmers. This study aims to analyze the regulation of agricultural land ownership within Indonesia's agricultural legal framework related to farmer protection, examine the factors causing inequality in land ownership that remain challenges in efforts to protect farmers under Indonesian agricultural law, and examine the role of Indonesian agricultural law in addressing inequality in land ownership to achieve equitable protection for farmers. The method used is normative legal research with a statutory and conceptual approach. Primary and secondary legal materials are analyzed qualitatively to assess the consistency of norms and the political direction of agrarian law. The results show that although Indonesian agrarian law normatively contains instruments for limiting and equalizing land ownership, inequality persists due to weak implementation, regulatory disharmony, and ambiguous policies between redistribution and investment. Protection of farmers in agricultural law depends on the state's consistency in internalizing the principles of social justice in the substance, institutions, and agrarian policies so that the law functions not only to regulate, but also to transform conditions of inequality in land ownership.